PENGARUH KONTEN @JENIUSCONNECT DI MEDIA SOSIAL INSTAGRAM TERHADAP BRAND AWARENESS APLIKASI JENIUS BTPN - MARIA ALVITA, NANCY (2020)
This technology development and research are motivated by Jenius BTPN as a pioneer of digital banking services, which still has challenges in increasing brand awareness and must improve itself to maintain its existence among competitors. With internet technology support, Jenius BTPN improves all aspects of its company, including the communication aspect. This strategy is strengthened by the active management of social media, one of which is by managing an Instagram account. This research is quantitative explanative and uses a survey method. The survey was conducted on 100 followers of @jeniusconnect. The result of the correlation coefficient is r = 0.675 with this value included in the level of a "strong" relationship because it lies between 0.600-0.799. The analysis of the results of the regression test shows that the X variable does not change and the Y variable is 19.222 because b is positive, the number of variable Y increases by 1.106. Analysis of the coefficient of determination test results of 45.5%, it can be concluded that 45.5% of Jenius BTPN brand awareness is influenced by Instagram content. The results of hypothesis testing using a significance level of 10% obtained a result of 1.661 with t table is 9.897 based on this calculation. The calculation results from the t count> t table are 9.897> 1.661, it can be concluded that H0 is rejected and Ha is accepted. Key Words: Marketing Communication, Social Media Content, Social Media Marketing, Brand Awareness